Enhancing regional resilience for energy price shocks: Efficient gas use and upstream decarbonization - Sacha J. den Nijs; Mark Thissen (Tinbergen Institute, 2024)
Resilience and competitiveness in relation to fossil energy dependencies is of increasing concern to industries and policy makers. We investigate to what extent the competitive position of industries in European regions are sensitive to changes in fossil fuel prices, and whether reductions in gas use along the value chain may increase regional industry resilience. A new spatial revealed cost competition model based on the input-output price model is used and calibrated to multi-regional world input-output tables on an EU NUTS 2 level. We obtain elasticities of fossil fuel prices on revealed cost competitiveness and analyze how they are affected by increased efficiency and electrification in production. We show that European regions are resilient to global coal price increases, whereas they are vulnerable to gas price shocks. The transition towards using less gas in production, by efficiency improvements or electrification, can reduce these gas price vulnerabilities. However, when competitors become more efficient instead, the vulnerability to such shocks may increase. Decarbonizing upstream sectors like electricity generation in the own region, own country or in Europe, can increase resilience of downstream industrial sectors in most European regions.
Keywords: F18; Q41; R11; R15; 330; Competitiveness; regional resilience; fossil fuels; energy efficiency; global value chains; input-output analysis